Respuestas

2012-04-15T01:54:40+02:00

9x2 + 6x + 10 = 0        a = 9, b = 6, c = 10

3x2  9x  + 0  = 0        a = 3, b = 9, c = 0  (el cero, la c, no se escribe, no está)

6x2 + 0x + 10 = 0       a = -6, b = 0, c = 10 (el cero equis, la b, no se escribe)

9x2 + 6x + 10         a = 9, b = 6, c = 10

3x2  - 9x                 a = 3, b = -9, c = 0

-6x 2 + 10              a = -6, b = 0, c = 10 
  3x*2+5x+4=0

4x*2+x+2=0

x*2+8x+12=0


7x*2+2=0 ( de la forma ax*2+c=0)

2012-04-15T03:24:14+02:00

9x2 + 6x + 10 = 0        a = 9, b = 6, c = 10

3x2  9x  + 0  = 0        a = 3, b = 9, c = 0  (el cero, la c, no se escribe, no está)

6x2 + 0x + 10 = 0       a = -6, b = 0, c = 10 (el cero equis, la b, no se escribe)

9x2 + 6x + 10         a = 9, b = 6, c = 10

3x2  - 9x                 a = 3, b = -9, c = 0

-6x 2 + 10              a = -6, b = 0, c = 10 
  3x*2+5x+4=0

4x*2+x+2=0

x*2+8x+12=0

 

7x*2+2=0 ( de la forma ax*2+c=0)